A REVIEW ON ANCIENT CONCEPTS OF KUMARAGARA, KRIDABHOOMI AND KRIDANAKA W.S.R.TO PEDIATRIC CARE UNIT, PLAY GROUND AND TOYS - Kanzode, *Sonam P; Kori, V K; S, Rajagopala; Patel, K S (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda is one of the earliest medical systems that have got a strong scientific foundation formulated by experiments and observations of ancient wisdom. Kaumarbhritya (pediatrics) is one among eight branches of Ayurveda. Acharya Kashyapa has given prime importance to Kaumarbhritya for the very first time. As far as the branch pediatrics is concerned, in Ayurveda it accompanies a broad area. Virtually every aspect of a growing child is connected with play. Now days, many textbooks of pediatrics are focusing more on pediatric diseases and its management, but the concept of toys, play and its importance remain untouched. Years ago, Acharyas has described characteristics of Kumaragara (Neonatal care unit/pediatric ward), Kumaradhara (guardian), Kridanaka (toys) and Kridabhumi (play ground) which all are the pillars of a healthy and prosperous human being. Here, an effort is made to collect those aspects and validating that data with available evidence based references.